ANÁLISE DO HÁBITO ALIMENTAR DE MACROBRACHIUM PANTANALENSE, SANTOS, HAYD & ANGER, 2013 (CRUSTACEA: PALAEMONIDAE) EM UMA LAGOA ARTIFICIAL DO PANTANAL DE AQUIDAUANA - MARTINS, Allex Sandro Durã; NAKAGAKI, Jelly Makoto (ANAIS DO ENIC, 2017)
-